HYGIENIC REQUIREMENTS IN UPPER JAW IMPLANTATION AND THEIR CLINICAL SIGNIFICANCE - Olimbayev Bekzodjon Muzaffar o‘g‘li (Web of Journals Publishing, 2026)
The article discusses hygienic requirements in maxillary dental implantation, including pre- and postoperative sanitary measures, aseptic and antiseptic protocols, and the impact of oral hygiene on implant success. Based on clinical observations and literature review, enhanced hygienic control significantly reduces peri-implantitis and postoperative complications.
Keywords: Maxilla, dental implantation, hygiene, asepsis, antisepsis, peri-implantitis, sinus lifting.